PENGENALAN PERMAINAN SIMAR SEBAGAI UPAYA MENGEMBANGKAN KETERAMPILAN DAN DISPOSISI MATEMATIKA PADA SISWA SEKOLAH DASAR DI KECAMATAN INDIHIANG - karlimah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Mathematics education in elementary schools still faces serious challenges, particularly in terms of student engagement and the development of positive mathematical dispositions. Conventional approaches that emphasize memorization and problem-solving exercises often lead to boredom and anxiety in learning. To address these issues, this community service activity aims to enhance teachers' capacity to implement the Simar game as an innovative, enjoyable, and contextual mathematics learning tool. The activity was conducted in Indihiang Subdistrict, Tasikmalaya City, involving 50 teachers from 19 elementary schools. The implementation method used the Outcome Mapping approach with five main stages: vision-mission formulation, invitation distribution, training, focused group discussions (FGD), and dissemination of results. The training consisted of presentations on game-based learning and mathematical dispositions, followed by hands-on practice with the Simar game. The results of the activity showed that teachers gained new insights into game-based learning concepts and demonstrated high enthusiasm in applying them. This activity also fostered teachers' critical awareness of the importance of participatory and meaningful learning. Thus, the Simar game has proven to be a promising educational tool that supports the development of cognitive skills and positive attitudes toward mathematics. Keywoard: Game-Based Learning, Mathematical Disposition, Simar Game, Mathematics Learning, Elementary School.